(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Basra Ports represent the only artery of Iraq, which contribute effectively to the development of the economic and social sectors. Despite the many existed research studies that dealt with the implementation public and private partnership (PPP) and their roles in achieving growth and development in the economic activities they were not adequately addressed the extent to which the performance and capability the management of PPP projects in the ports of Iraq were evaluated and determined their problems. This study aims to design a frame work for assessment the readiness the management of PPP projects in Iraq’s ports, and how to improve their performance in order to enhance the PPP contributions in economic development. The study investigated the perceptions of a sample of 76 managers of ministries of planning , transportation , general Company for ports Of Iraq and PPP decision makers in order to evaluate and assessment the readiness of the management of public private partnerships in Iraqi ports by designing questionnaires and then investigated all 57 managers of these PPP in order to illustrate problems which obstacle their work and improve the performance of their Companies of partnership projects contracting with Basra general company for ports(BGCP)of Iraq. The output was Shown that the readiness of the management of PPP was below the acceptable level and suggested which determined by World Bank and suggested ways to address the PPP for enhancing and to be more effective in the process of economic development in Iraq and can manage and bid for developing the Grand Al Faw port which will be the greatest port in the middle east , the research illustrated problems facing the PPP and suggested ways to tackled the problems in order that PPP will be more capable for operating ports process.